Implementing Inquiry-based Learning through Sustainable Development Goals: A didactic Approach to Foster Learn-ing-to-learn and Citizenship Competencies in EFL - Miryam Bravo Luque; María Alcantud-Díaz (Papeles)
Introduction: This study employs a mixed-method approach to examine the integration of the Inquiry-Based Learning (IBL) approach with the thematic framework of the Sustainable Development Goals (SDGs). Methodology: Conducted in a fourth-year secondary school EFL class at a state school in Spain, the research focuses on a didactic implementation spanning three sessions. This initiative addresses the societal need to make classes more engaging and impart knowledge about our planet’s current state and society. Results and Discussion: Despite limitations in time and the number of participants, the results indicate that IBL, when combined with Agenda 2030, provides numerous benefits. These benefits include motivating students to engage in their learning process actively, enhancing communication through active participation, and fostering a sense of optimism about potential outcomes. Conclusions: The findings, derived from both qualitative and quantitative data, offer significant contributions to the field of education, particularly EFL, by demonstrating that the methodological alternatives and thematic focus can help students form meaningful connections with their learning, thereby increasing their involvement in their studies.